Research on Sidewall Interference Control in Airfoil Wind Tunnel Test Based on Vortex Generator - WEI Binbin; GAO Yongwei; SHI Yao; LI Dong; HAO Lishu (Hangkong gongcheng jinzhan, 2021)
The wind tunnel sidewall boundary layer needs to be controlled since the sidewall interference in the wind tunnel test of the large-thickness airfoil is serious.In this paper, passive vortex generators(VG) are used at first time to control the sidewall interference effect on the large-thickness airfoil FX77-W-400, and two VG-based sidewalls interference control configurations are proposed, i.e.sidewall VG and airfoil VG.The effects of the VG installation position on the airfoil aerodynamic performance and pressure field details are studied, and the proper orthogonal decomposition(POD) is used to study the airfoil surface pressure field structure.The research shows that:the passive VG used in this work can effectively control the sidewall interference.The peak suction of the airfoil surface is affected by sidewall VG and airfoil VG.There is a significant linear correlation between the lift coefficient and the peak suction within the scope of this study.The sidewall interference control method used in this work maintains the main structure of the reference airfoil surface flow.The research is of certain guiding significance for the wind tunnel test and theoretical research.